UNLICENSED MEDICAL PRACTICE AND INSTITUTIONAL SILENCE: A CASE STUDY ON PMDC’S INEFFECTIVE RESPONSE AND THE IMPLICATIONS FOR PUBLIC HEALTH AND NATIONAL INTEGRITY. - Siddiqui, Hassan Rasheed (The journal of contemporary issues in business and government, 2024)
The most critical issue of unauthorized practice of medicine by unregistered individuals is claiming to be registered medical practitioners/military personnel has turned into major area of public health concern in Pakistan. With a particular lens on impersonation and quackery, this research elaborates upon the systemic issues that exist when it comes to keeping doctors in check, and questions whether PMDC is the right institution to undertake this responsibility. Adopting a qualitative approach, interviews were conducted comprising 10 health care employees, 10 medical fraud victims, and 10 regulatory authorities, through using case studies. Furthermore, secondary data from local reports, media articles and related literature were examined to better understand this issue. [The study found several serious issues, such as the PMDCs informal enforcement of medical laws, illegal use of military grades by impostors and the adverse effects on patient health as well as resulting institutional disgrace.] Results: Thematic and narrative analyses of interview data revealed that both victims and health care practitioners harbored serious concerns about the emergence of quackery and the limited measures that regulatory bodies were taking to address it. The paper suggests several policy solutions to curb these issues such as enhancing the verification process, making it illegal to impersonate military ranks, introducing a public black book, and increasing public awareness about unqualified practitioners. According to its analysis, Pakistan can combat the growth of illegal medical practice, safeguard public health, and regain trust in its healthcare systems by enhancing regulatory monitoring and legal action.